2007
DOI: 10.1038/sj.onc.1210717
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase-α phosphorylation by Src on Y335 is required for activation, membrane recruitment and Hgf-induced cell motility

Abstract: Diacylglycerol (DAG) kinases (Dgk), which phosphorylate DAG to generate phosphatidic acid, act as either positive or negative key regulators of cell signaling. We previously showed that Src mediates growth factors-induced activation of Dgk-a, whose activity is required for cell motility, proliferation and angiogenesis. Here, we demonstrate that both hepatocytes growth factor (HGF) stimulation and v-Src transformation induce tyrosine phosphorylation of Dgk-a on Y335, through a mechanism requiring its proline-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 40 publications
(69 reference statements)
1
47
1
Order By: Relevance
“…PKA and PKC have been shown to phosphorylate DGK in COS7 cells ( 85 ). Phosphorylation of DGK ␣ by the tyrosine kinase Src confers hepatocyte growth factor-induced cell motility ( 86,87 ), whereas PKC-catalyzed phosphorylation of DGK promotes the dissociation of the lipid kinase from PKC ( 88,89 ). Given that DAG stimulates PKC activity, the association with DGK provides a mechanism to limit the ability of PKC to phosphorylate target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PKA and PKC have been shown to phosphorylate DGK in COS7 cells ( 85 ). Phosphorylation of DGK ␣ by the tyrosine kinase Src confers hepatocyte growth factor-induced cell motility ( 86,87 ), whereas PKC-catalyzed phosphorylation of DGK promotes the dissociation of the lipid kinase from PKC ( 88,89 ). Given that DAG stimulates PKC activity, the association with DGK provides a mechanism to limit the ability of PKC to phosphorylate target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with overexpressed enzyme suggest that DGK␣ Y335 phosphorylation targets DGK␣ to the plasma membrane (37,38). Analysis of endogenous protein in Jurkat T lymphocytes demonstrates that tyrosine-phosphorylated DGK␣ represents a membrane-associated fraction, which probably corresponds to the active pool of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological significance of this rapid loss of association remains to be determined, but it may favor DGK␣ association with other partners. A recent publication showed that phosphorylated Y335 might interact with certain SH2 domains in vitro (37). The rapid dissociation of DGK␣ pY335 and Lck might also control and/or restrict an inhibitory DGK␣ effect on Lck activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that DGKα is activated by growth factors on recruitment to the plasma membrane through its Src-mediated phosphorylation on Tyr 335 . Activation of DGKα mediates growth-factor-induced cell migration and proliferation in epithelial, endothelial, and lymphoma cells (8)(9)(10)(11)(12). Moreover, we demonstrated that in epithelial cells, DGKα is required for hepatocyte growth factor (HGF) -induced membrane ruffling by regulating Rac membrane targeting and activation (13).…”
mentioning
confidence: 99%